Cinema of the Not-Yet: The Utopian Promise of Film as Heterotopia - Ivakhiv, Adrian (Journal for the Study of Religion, Nature and Culture, 2011)
Drawing on Ernst Bloch’s writings on utopia, Michel Foucault’s notion of heterotopia, and the ‘affective turn’ in social theory, I argue that cinema is by its nature heterotopic: it creates worlds that are other than the ‘real world’ but that relate to that world in multiple and contradictory ways. The landscapes and people portrayed in ?lm are affectively charged in ways that alter viewers’ relationship to the real objects denoted or signi?ed by them. But it is the larger context of social and cultural movements that mobilizes or fails to mobilize this affective charge to draw out its critical utopian potentials. I examine four ?lms from the 1970s—Deliverance, The Wicker Man, Jonah Who Will Be 25 in the Year 2000, and Stalker—as examples of richly heterotopic ?lms that elicited utopian as well as dystopian affects in their audiences, and I discuss some ways in which American environmentalists, British Pagans, Europe’s ‘generation of ’68’, and Soviet citizens worked with these affects to imagine change in their respective societies.